An internet-delivered psychoeducational intervention (Fex-Can 2.0) targeting fertility-related distress and sexual dysfunction in young adults diagnosed with cancer: Study protocol of a randomized controlled trial with an internal pilot phase - Rebecca Skog; Erik M.G. Olsson; Jessica R. Gorman; Sharon L. Bober; Claudia Lampic; Lena Wettergren (PLoS ONE, 2025)
Background While previous literature has continuously demonstrated the negative effects of cancer and its treatment on fertility and sexuality, evidence-based interventions to alleviate fertility-related distress and sexual dysfunction are lacking. This study protocol describes the internal pilot study and randomized controlled trial of an internet-delivered psychoeducational intervention: Fex-Can 2.0. The primary objective is to determine efficacy of Fex-Can 2.0 in terms of reduction of fertility-related distress and sexual dysfunction at end of the 12-week intervention. The internal pilot study will assess feasibility of the study, determined according to pre-specified progression criteria and individual interviews. Methods The study has a randomized controlled design, with an internal pilot phase. The intervention group will receive Fex-Can 2.0, consisting of psychoeducational- and behavior change content. The control group will be allocated to standard care. Primary outcomes are fertility-related distress (RCAC) and sexual function and satisfaction (PROMIS SexFS Brief Sexual Profile). Secondary outcomes include body image (BIS), emotional distress (HADS), health-related quality of life (EORTC QLQ-C30), need satisfaction and frustration scale (NSFS), fertility- and sex-related knowledge, and self-efficacy related to fertility and sex life. Outcomes will be assessed at baseline, directly after the intervention, and 12 weeks later. During the internal pilot, data on trial recruitment, data collection, drop out, and adherence will be collected to assess feasibility. Semi-structured interviews will be conducted to further assess acceptability of Fex-Can 2.0. Conclusions This randomized controlled trial aims to evaluate whether Fex-Can 2.0 is superior to standard care, in terms of reducing fertility-related distress and sexual dysfunction in young adults diagnosed with cancer. If proven efficacious, the Fex-Can 2.0 intervention may be a valuable resource in health care, with the potential to significantly improve the care of young adults experiencing fertility-related distress and/or sexual dysfunction following cancer. Trial registration ClinicalTrials.gov ISRCTN18040643